Imaging and Sensing for Unmanned Aircraft Systems. Volume 1 : Control and Performance - Estrela, Vania V.; Hemanth, D. Jude 1981-; Saotome, Osamu; Nikolakopoulos, George; Sabatini, Roberto (Institution of Engineering and Technology, IET, 2020)
UAV avionics aim to boost flight visibility and situational awareness. This book intends to be a reference for vision and sensor integration. It will display fundamental aspects, ongoing research efforts, accomplishments, and challenges faced when it comes to the deployment of imaging capabilities and sensor integration in UAVs
Keywords: imaging capabilities; sensor and vision integration; UAV avionics; Image processing / Equipment and supplies; autonomous aerial vehicles; image sensors